Evaluation of the Implementation of Independent Curriculum in Geography Learning in State Senior High Schools in Gorontalo City - Limonu, Rusli; Fitryane Lihawa; Masrid Pikoli (International journal of technology and education research, 2026)
This study aims to evaluate the implementation of the Independent Curriculum in Geography learning in State High Schools throughout Gorontalo City using the CIPP (Context, Input, Process, Product) evaluation model. Context evaluation is carried out to assess the readiness of the school environment and supporting policies; Evaluation of inputs assesses the readiness of teachers and learning facilities; process evaluation assesses the implementation of learning in the classroom; and product evaluation assesses student learning outcomes. This study uses a descriptive quantitative approach with data collection techniques in the form of observation, questionnaires, documentation, and document studies. The results of the study showed that: (1) the context evaluation obtained an average of 89.18% and was in the good to very good category, indicating the readiness of the institution in adopting the Independent Curriculum; (2) the average input evaluation of 89.55%, showing the readiness of teachers and the availability of adequate resources, even though there are teachers who get low scores; (3) the evaluation process showed the highest achievement with an average of 96.73%, illustrating that teachers are able to implement differentiated learning, formative assessment, and student-centered approaches effectively; and (4) product evaluation showed that the average score of students in all schools was above the KKTP (75), with the highest achievement at SMA Negeri 3 Gorontalo (87.66). The implementation of the Independent Curriculum in Geography learning has been carried out very well, but it is still necessary to strengthen teacher training and equalize the quality of implementation between schools. Keywords: Evaluation, Independent Curriculum, CIPP, Geography, High School